دور المحاسب العمومي في الرقابة على انفاق الهيئات الحكومية الجزائرية – قراءة تحليلة لقانون المحاسبة العمومية . - عنتر, سليمان; مايدة, محمد فيصل; سباع, احمد الصالح (جامعة الوادي- University of Eloued, 2017)
This research deals with the definition of public accountant role in monitoring the implementation of public expenditure for the Algerian government bodies under the public accounting law, which regulates the accounting practices in governmental bodies and institutions, which centerd on the collection of revenue and expenditures, where endanger public accountant plays a key role in these practices, especially in connection with the construction of the monitoring of the implementation of public expenditure, through a set of rules and procedures that help to detect errors and abuses that can be deficiencies in the disbursement of public money this kind of bodies.
مقال
Keywords: Public accountability, public accountant, public revenues, public expenditures